Comparative study of roof truss construction method in Malaysia - Mohd Sani, Mohd Syahrul Hisyam (2004)
The first light frame trusses were built on site using nailed plywood gusset plates. These trusses offered acceptable spans but demanded considerable time to build. In the 1950’s the metal connector plate transformed the truss industry by allowing efficient prefabrication of short and long span trusses. With the growing demand for affordable housing, increasing construction costs and heightened concern for energy-efficiency, contractors and builders across Malaysia have recently begun to re-examine their options for the delivery of housing. Roof trusses come in all shapes and sizes to suit almost every single design of roof. This trend has resulted in a growing interest in prefabricated building system including roof truss systems. Both prefabricated roof truss systems and onsite roof truss construction are used currently. From this two system, many macroeconomic factors and regulatory factors like speed of construction and use advanced technology have been cited as reasons for this, little attention has been paid to the nature of the homebuilding industry, its operational structures and the ability of the product itself to accommodate the contractor’s needs and preferences. From these two methods, the site observation, interview and questionnaire data are been analysed from the characteristic factors that involve in roof truss construction. All the parties that involve in construction industry like roof truss manufacturers, contractors and consultants are being interviewed and asked about the roof truss system. Finally the result that been generated is show that the prefabricated system is the most popular system and give many advantages to Malaysian construction industry.